Early detection of cervical tumor cell of origin through Oncogene-induced senescent HPV-positive cells: Oncogene-induced senescent HPV-positive cells - Al-Rawi, Rafal Abdulrazaq (Cellular and Molecular Biology, 2024)
Human Papilloma Virus (HPV) is an oncogenic virus and is the most common cause of cervical cancer. HPV has been shown to induce senescence. Cellular senescence is involved in cancer progression and tumorigenesis. Identification and isolation of cells of tumor origin before tumorigeneses is an important step in cancer prevention and treatment. This study aimed to investigate the early cervical atypical senescent cytological preneoplastic change in non-menopausal women. Cervical smears of 121 patients were randomly selected and included in the study which cytopathologically diagnosed as atypical squamous cells of undetermined significance (AS-CUS) in correlation to HPV status, parakeratosis (PK), p16 immunostaining, enlarged Squamous cells nuclei (ES) and inflammatory cells infiltration (ICI). Results revealed that out of the total 121 patients, 32 cases (26%) were positive for high-risk HPV (HR-HPV), 26 cases (22%) were positive for low-risk HPV (LR-HPV) and 63 (52%) were negative for HPV. HPV infections were significantly associated with age groups (p<0.026), PK (p = 0.043), p16 (p = 0.001), ES (p = 0.002) and ICI (p = 0.049). The positive immunostaining expression of p16 was only noticed in two HR-HPV patients. ES cells were found in 9.5% of HPV-negative cases, 27% of LR-HPV cases and 40.5% of HR-HPV cases. High PK cell positivity was seen only in HR-HPV. High ICI scores were seen in 40.6% of HR-HPV patients, 26.9 % of LR-HPV and 17.4 % of negative HPV patients. It was concluded that high PK positivity, high ICI score, positive p16 immunostaining and ES were correlated with HR-HPV in non-menopausal women. These findings could provide potential diagnostic clues for HPV-harboring senescent cells as a strategy for reducing HPV risk of cervical cancer development and identifying the cell of tumor origin, which could be beneficial for improving the utility of senolytic agents and immunotherapy in clinical practice.